Making Traditional Ingredients of Green Coconut Oil as a Facility for Medical and Non-Medical Treatment in Tembung, Percut Sei Tuan District - Fadli, Muhammad; Suharyanto, Agung; Maswita, Maswita; Bahri, Samsul; Febryani, Ayu; Parinduri, Wina Mariana (Program Studi Antropologi Sosial Pascasarjana Universitas Negeri Medan, 2023)
This study aims to analyze the prevalence of individuals choosing traditional medicine for both medical and non-medical treatment, emphasizing the unwavering faith of the Tembung community in the efficacy of traditional medicine, particularly green coconut oil, and herbal remedies. The literature review is anchored in the concept of preserving local wisdom in traditional medicine. Employing a qualitative research approach with an ethnographic lens, the author conducted data collection through observation, in-depth interviews, and documentation, utilizing Spradley's model for analysis. The findings reveal the persistent utilization of ancestral herbal remedies in traditional medicine, driven by ingrained beliefs and financial considerations, particularly as a cost-effective alternative for both medical and non-medical ailments. In summary, the study concludes that the community's strong belief in traditional medicine is rooted in its affordability and accessibility, allowing individuals to seek treatment without bureaucratic hurdles. The paper underscores the importance of government support and monitoring to ensure that traditional medicine aligns with regulations, fostering a sense of security for those seeking treatment within these practices. It is recommended that the government continues to collaborate with traditional medicine practices, ensuring a balance between cultural preservation and adherence to established standards.